RELATIONSHIP OF FOLKLORE AND LITERATURE - Nargis Fagimovna Shagiyeva (Web of Journals Publishing, 2024)
The interdependence of folklore and literature is an urgent problem of current literary criticism in the aspect of the formation of world culture. An important task of modern science involves identifying difficult ones. unique, historically determined patterns of literature's appeal to folklore in different eras. the concept of the dynamics of these connections.
Keywords: folklore, literature, relevance, problem, literary criticism, aspect, world culture, modern science, pattern, different eras, dynamics of connections.